A family member's death increases religious activity: Evidence from Germany - Tim Friehe; Christian Pfeifer (Kyklos, 2024)
Religiosity influences economic behavior in various domains, but what determines religiosity? Using data from the representative Socio-Economic Panel Study for Germany (SOEP), this paper shows that religious activity increases after a family member's death. The life event's effect is larger after a partner's death when compared to a parent's death. Our results indicate that the influence of a family member's death on religious activity is temporary and are consistent with the religious coping hypothesis.
Keywords: 300